2015
DOI: 10.5120/ijca2015907177
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Data Transmission using Image Steganography

Abstract: Steganography can be defined as the science of hiding data behind images in such a way that no one except the sender and receiver has any idea about the transfer of hidden message taking place. In this paper, light is thrown on the algorithm using LSB of the image pixels to store data and transfer in a hidden manner, such that it won't attract attention and the observers will be unaware of any data transmission taking place. The project involved implement and compare three algorithms and evaluate the results t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Dharmesh Mistry, Richa Desai, and Megh Jagad explained that the Steganography cannot take the place of the cryptography but it supports the cryptography. They showed that if the steganography and the cryptography is used together the result will be getting double layer of security and protection and decrease the probability to detect the hidden data [15].…”
Section: Previous Studymentioning
confidence: 99%
“…Dharmesh Mistry, Richa Desai, and Megh Jagad explained that the Steganography cannot take the place of the cryptography but it supports the cryptography. They showed that if the steganography and the cryptography is used together the result will be getting double layer of security and protection and decrease the probability to detect the hidden data [15].…”
Section: Previous Studymentioning
confidence: 99%
“…This technique of hiding information by embedding other, seemingly harmless messages with our message to be transferred, Steganography employs the replacement of bits that apparently are useless or not used, with bits that contain some important, invisible data within it. The type of data that can be hidden ranges from plain and cipher texts to images [3]. • Secret Message: the information that you want to embed inside the cover media.…”
Section: Steganographymentioning
confidence: 99%